THE ROLE OF PHYSICS IN POLYMERS RECYCLING (American Journal of Interdisciplinary Research and Development, 2023)
Processing of polymers is the final stage of obtaining a product from it, and this product should be able to meet specific requirements.Therefore, along with the discovery of various methods, new polymer materials were developed. If we look at history, in the middle of the 19th century, equipment for vulcanization of rubber, methods of acetylation and nitration of cellulose appeared. About 100 years later, plastic processing methods, their improvement, and modeling of these methods on a physico-chemical basis began to appear, and as a result, it became the basis for the creation of a new science "Polymer processing technology". The technology of polymer processing includes the processes of obtaining rubber materials, preparation of varnish and paint, and formation of chemical fibers. Among them, the technology of plastic processing (and production) takes the main place.